Person, situation, and spin: Examining the correlates of interpersonal spin with mobile application-based ECR. (March 2021) - Clegg, Kayleigh-Ann; Moskowitz, D.S.; Miners, Christopher T.H.; Andrevski, Goce; Sadikaj, Gentiana
Abstract: Objective: Interpersonal spin refers to within-person variability in social behavior. Pen-and-paper Event-Contingent Recording (ECR) has typically been used to measure spin, establish its reliability, and explore its relation with personality characteristics and variability in situational features. The present study aims to replicate these studies using mobile application-based ECR. Method: 267 students participated in a 20-day ECR procedure, reporting on social interactions via mobile application. Five-factor traits were measured pre-ECR using self-report. Spin scores and situational features were assessed across interpersonal interactions. Results: The reliability of spin scores was substantial but was lower than in previous studies. We partially confirmed previous findings, demonstrating that spin is predicted by Neuroticism, although the effect was smaller than in previous studies, and not meaningfully predicted by variability in external situational features. Conclusions: The present study provides some support for an application-based ECR procedure to collect data about within-person variability in social behavior. Practical and procedural advantages and limitations of this method are discussed. Differences in reliability and effect sizes between the present study and previous studies raise important considerations for future research.